Enterprise Surveys : Paraguay Country Profile 2017 - World Bank (World Bank, Washington, DC, 2018)
The Enterprise Surveys (ES) focus on many aspects of the business environment. These factors can be accommodating or constraining for firms and play an important role in whether an economy’s private sector will thrive or not. Questions contained in the ES aim at covering most of the topics mentioned above. The topics include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, access to finance, innovation, labor, and perceptions about obstacles to doing business. This document summarizes the results of the Enterprise Survey for Paraguay. Business owners and top managers in 364 firms were interviewed between February and August 2017. The report provides a description of the sample breakdown across the three survey design categories: business sector, firm size, and location.